Long-Term Survival Following Cladribine Containing Pretransplant Regimen for Autologous Hematopoietic Stem Cell Transplantation in Disseminated Interdigitating Dendritic Cell Sarcoma: A Case Report and Literature Review - Zhou P; Nie L; Ma R; Wang X; Wu G; Zhu Z; Yuan X (Journal of Blood Medicine)
Pan Zhou,1 Lu Nie,1 Rongjun Ma,1 Xiaoyan Wang,2 Guangyin Wu,3 Zunmin Zhu,1 Xiaoli Yuan1 1Department of Hematology, Henan Provincial People’s Hospital, People’s Hospital of Zhengzhou University, Zhengzhou, 450003, People’s Republic of China; 2Department of Pathology, Henan Provincial People’s Hospital, People’s Hospital of Zhengzhou University, Zhengzhou, 450003, People’s Republic of China; 3Department of Radiotherapy, Henan Provincial People’s Hospital, People’s Hospital of Zhengzhou University, Zhengzhou, 450003, People’s Republic of ChinaCorrespondence: Xiaoli Yuan, Email yuanxiaoli@126.com Zunmin Zhu, Email zhuzm1964@163.comAbstract: Interdigitating dendritic cell sarcoma (IDCS) is an exceedingly rare hematological neoplasm arising from dendritic cells that presents significant diagnostic and therapeutic challenges, particularly in cases of disseminated disease. Here, a 33-year-old woman presented with discomfort of the left pharynx accompanied by nasopharyngeal and cervical mass for 3 months. The histopathology confirmed the diagnosis of IDCS as the neoplastic cells were spindle or ovoid in shape, forming fascicles or whorls, and were positive for S-100, vimentin and CD163 but negative for CD21, CD23, CD35 and CD1a. The patient underwent autologous hematopoietic stem cell transplantation (auto-HSCT) after achieving partial remission (PR) from six courses of chemotherapy based on the ABVD regimen and one cycle of radiotherapy. Encouragingly, the mass disappeared after cladribine containing regimen pretreated auto-HSCT and the patient has been in complete remission (CR) state for over 5 years. Therefore, the long survival of this patient might suggest that ABVD regimen with a sequential cladribine-containing preparative regimen prior to auto-HSCT may improve the prognosis of disseminated IDCS. However, this represents only a single-case experience, and further studies with larger sample sizes are required for validation.Keywords: disseminated interdigitating dendritic cell sarcoma, autologous hematopoietic stem cell transplantation, ABVD regimen, cladribine, survival